Tourism development trajectories- From culture to creativity? - Richards,Greg (2010)
This paper traces the development of creative tourism as new form of cultural tourism. This trend has been stimulated by the growth of new consumption patterns, by more involved and skilled forms of tourism activity, and by changes in the production of tourism, such as the development of the experience economy. Arguably creative tourism also provides some answers to the increasing problems experienced in cultural tourism development, which is rapidly becoming another form of mass tourism. The paper outlines the different forms that creative tourism can take, ranging from interactive workshops and learning experiences to creative backdrops for tourism activity. Illustrations of creative tourism forms are taken from creative tourism networks, workshops, creative spaces, cultural itineraries and creative events.